Intensive diabetes management - Wolfsdorf, Joseph I.; American Diabetes Association (Alexandria [Va.] : American Diabetes Association, 2012)
'This is the most current and practical book available on how to begin and maintain intensive diabetes management'--Provided by publisher.
Includes bibliographical references and index.
Keywords: Diabetes mellitus -- Therapy; Diabetic Diet; Insulin -- administration & dosage; Patient Education as Topic; Self Care -- methods